Dari Komunitas ke Kapital: Analisis Modal Sosial dalam Pembentukan Ekosistem Startup di Kota Makassar - Arsyad, Ernawati; Syukur, Muhammad (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2025)
The startup ecosystem in Makassar, as the economic node of Eastern Indonesia, faces a sustainability puzzle amid limited formal resources. This study aims to analyze how Social Capital (trust, norms, and networks) influences founder access to vital resources (seed capital, mentors) and to identify the dynamics of embeddedness and power structure within the ecosystem. Employing a Qualitative approach with an Analytical Case Study design, based on Thematic Synthesis and Cross-Case Analysis of secondary data and academic literature, the study finds that Social Capital is dualistic: both a fundamental asset and a structural hindrance. Strong ties (bonding ties), reinforced by the pacce culture, create relational trust that acts as an institutional substitute for early-stage funding access and reduces transaction costs. However, the ecosystem is hindered by limited bridging ties, the risk of over-embeddedness leading to moral hazard, and power conflicts/structural silos that impede inclusivity and scalability. It is concluded that the ecosystem's maturation requires hybrid intervention that structurally institutionalizes bridging ties (e.g., through boomerang migration) and balances social embeddedness with professional disembedded mechanisms.